PERCUTANEOUS NEPHROSTOMY FOR OBSTRUCTIVE UROPATHY MANAGEMENT IN CERVICAL CARCINOMA - Yusuf, Muhlis; Yogiswara, Niwanda; Soetojo (Indonesian Urological Association, 2022)
Objective: This study aims to evaluate the role of percutaneous nephrostomy (PCN) in treating patients with hydronephrosis due to complications of cervical cancer. Material & Methods: This research was a retrospective analytical cohort study. All medical record data of patients with a diagnosis of cervical carcinoma and undergoing percutaneous nephrostomy at Soetomo General Hospital in 2017 – 2020 were collected and analyzed. Results: A total of 45 subjects were included in this research. The mean age of the subjects was 55.07, with the youngest being 34 years old and the oldest being 75 years old. Most of the subjects were stage IIIB cervical carcinoma (95.56%), and the rest were stage IIB. Contralateral PCN was required in 75.56% of subjects, and the rest only required unilateral PCN. Before being PCN performed, some patients had moderate HN (64.4%), and after the patients underwent PCN procedure, the majority of patients had the HN resolved (48.89%) (p<0.05). There was also an improvement in the laboratory parameter of urea and creatinine serum before and after PCN (p<0.05). Conclusion: PCN improves the laboratory and radiologic parameters of cervical cancer patients with hydronephrosis.